Implementasi Penerangan Jalan Umum Berbasis Solar Cell untuk Peningkatan Keamanan Lingkungan di Widoro I Kelurahan Sembungharjo Genuk Kota Semarang - Ahmad, Fahrudin; Pramuyanti, Roni Kartika; Cahyono, Taufiq Dwi (Faculty of Engineering, Universitas Semarang, 2026)
The lack of adequate lighting in Widoro I – Perbalan 3 increases security risks and limits community activities at night. This program provides an independent and sustainable street-lighting solution through the installation of a 1500 W portable solar-powered street lighting (PJU) system. The implementation method integrates the diffusion of appropriate technology, training, and the ABCD approach to ensure technical sustainability and community involvement. The activities include a needs survey, technical planning, installation, socialization, and monitoring. The results indicate an increase in illuminance from 2–3 lux to 25–30 lux, a panel efficiency of 21%, and the availability of backup power for up to three days. The motion sensor system has been proven to improve energy efficiency and expand lighting coverage. Socially, the program increases nighttime activities by 65% and enhances perceptions of environmental safety. This program demonstrates that the application of portable solar-powered street lighting can serve as an effective, efficient, and replicable appropriate-technology model for residential areas with limited access to energy. These findings emphasize the importance of synergy between renewable energy technology and community empowerment to achieve local energy independence.